Public Health Nutrition: Rural, Urban, and Global Community-Based Practice. Margaret Barth et al. (Epidemiology, Biostatistics, and Public Health, 2024)
Although this book originally intended as an introductory text for the education of future public health nutrition practitioners, it has evolved to forge and aspire public health nutrition leaders.
Keywords: Public health; Nutrition Assessment; healthy eating policy; evidence-based policy-making